Association of power at VO2peak and anaerobic threshold with rank in British high performance junior surfers - Barlow, M. J.; Gresty, K.; Findlay, M.; Cooke, C. (Human Movement, 2015)
The objective of this study was to determine the relationships of peak oxygen uptake ( O2peak), power at O2peak and power at the anaerobic threshold (AT) with national ranking in a sample of British high performance junior surfers. Methods. Eighteen male surfers (aged 15.4 ± 1.4 years) from the British Junior Surfing team were tested for O2peak and AT using an adapted kayak ergometer; national ranking was used to indicate performance level. The AT was identified as the point at which E/ O2 started to rise without a concomitant increase in E/ CO2. Spearman`s rank (rs) and partial correlations (rp) controlling for age were used to identify the relationships between the physiological variables and national ranking. Results. Mean O2peak was 3.1 ± 0.5 l · min-1 (47.7 ± 7.2 ml · kg-1 · min-1) and mean AT occurred at 48.1 ± 12.2 W. There were significant correlations between national ranking and power at O2peak (rs = -0.549, p = 0.028), power at AT (rs = -0.646, p = 0.009), and age (rs = -0.579, p = 0.012). Significant partial correlations were established controlling for age between national ranking and power at O2peak (rp = -0.839, p = 0.000) and power at AT (rp = -0.541, p < 0.046). Conclusions. The power outputs associated with O2peak and AT were significantly related to surfer ranking in this sample. However, due to the low coefficient of determination associated with the AT/ranking relationship, AT does not discriminate well between the ranking of surfers. These findings support the inclusion of power at O2peak in assessment batteries for junior competitive surfers.